PENGARUH PENDAFTARAN ONLINE TERHADAP JUMLAH PENDAFTAR DI SEKOLAH DASAR NEGERI JAKARTA - Yahdi Kusnadi; - Mutoharoh (LPPM Universitas Bina Sarana Informatika, 2016)
New Student Registration Information System created to convey information about public elementary school to the public via the internet. In addition to prospective students who will enroll in elementary school can enable them to register online. But there are still many parents who do not understand the registration procedures online, and not optimal dissemination of the online registration in the community. To solve this problem the authors conducted research into elementary schools to obtain accurate data by using the method of observation, interviews and transmit kuesoner (questionnaire data). After all the data is collected penuis perform data processing using SPSS 17.0 software so that the results of this study can conclude that with their students online registration affect the number of applicants. With the results of analysis of variance to regression = 163.333 with a significance of 0.000 <0.05. So it can be decided that the research hypothesis (Ha) which states